Melt-driven erosion in microparticle impact - Mostafa Hassani-Gangaraj (Nature Portfolio, 2018)
Supersonic particle impacts can cause permanent damage to space vehicles and satellites, but how exactly remains unclear. Here, the authors visualise for the first time the high impact of single tin microparticles on a tin substrate and show erosion of ductile metallic materials is melt-driven.